Establishment of Mosque Economic Institution (UEM) at AlMuhajirin Mosque, Jatihurip Village - North Sumedang District, Sumedang Regency - Gunawan, Wawan (SINTESA, 2024)
This research aims to form a Mosque Economic Enterprise organization, hereinafter referred to as UEM, at the Al-Muhajirin mosque which aims to revive economic activities among mosque congregations, by managing alms funds. The definition of UEM is basically an institution that is engaged in economic activities owned by a mosque or under the Mosque Management Organization (Mosque Prosperity Council/DKM) to improve the welfare of the congregation/community in the mosque environment through collecting and managing alms funds to be distributed to the community around the mosque. in the form of consumptive/social assistance and productive in the form of non-interest bearing loans. Before the formation of UEM, socialization was first carried out to introduce UEM as an institution under the auspices of DKM with the aim of improving the welfare of the congregation/community in the mosque environment. After the socialization was carried out, the UEM institution was formed under the auspices of the DKM mosque, then one of the efforts to build UEM was to distribute piggy banks which were distributed to the congregation to raise capital funds for UEM.